Modern Pre-School Education from the Standpoint of Self-Worth Childhood - Shaikhelislamov, Rais F.; Shaekhova, Rezida K.; Murzalinova, Alma Zh. (Pedagogika, 2016)
Relevance of the studied problem is due to the reforming of the Russia education system that have begun in according to which the pre-school system is the first stage of general education and in this regard at the stage of practical implementation of reforms there is a risk of self-worth loss as the preschool period of development of the foundations of human culture in specific children’s activities. The purpose of the article is the theoretical justification of transition of childhood phenomenon from the information paradigm to the cultural-historical one, in refinement of “early childhood education” category in the context of the FSES, in disclosure of the idea of preschool self-worth. Leading approach to the theoretical justification of the author’s position is a cultural-historical system-activity approach. During the research process there are emerged number of important results: revealed and systematized the conditions for ensuring the childhood self-worth in the process of transformation of the system of preschool education into the stage of general education; was conducted the theoretical study of the need to preserve the specificity of preschool age as a basis for the formation of a full-fledged personality. Overall results of the study can help to solve the problem of formation the state educational policy aimed at improving the social status of preschool children, and may also be useful for developers of teaching materials of vocational and further education in the field of early childhood education.